Acute acalculous cholecystitis following extended administration of nirmatrelvir/ritonavir for persistent SARS-CoV-2 infection - Ito, Wataru; Fukumori, Tatsuya; Asaoka, Nao; Imakita, Natsuko; Nishimura, Tomoko; Furukawa, Ryutaro; Nishihara, Yuji; Fujikura, Hiroyuki; Sekine, Takahiro; Yamaguchi, Naoki; Hirata, Yuichiro; Miyamoto, Sho; et al. (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2024)
Immunocompromised patients with hematologic malignancies, particularly those treated with anti-CD20 antibodies such as rituximab and obinutuzumab, are known to be at risk of prolonged infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Prolonged administration or combination therapy with antiviral medications reportedly yields favorable outcomes in these patients. However, knowledge regarding the adverse events associated with such therapeutic approaches is limited. Herein, we report a case of acute acalculous cholecystitis (AAC) following extended administration of nirmatrelvir/ritonavir (NMV/r) in a 68-year-old Japanese man with persistent SARS-CoV-2 infection. The patient had received obinutuzumab and bendamustine for follicular lymphoma and was diagnosed with coronavirus disease 2019 (COVID-19) approximately one year after treatment initiation with these drugs. Subsequently, he was admitted to a different hospital, where he received antiviral drugs, monoclonal antibodies, and steroids. Despite these interventions, the patient relapsed and was subsequently transferred to our hospital due to persistent SARS-CoV-2 infection. Remdesivir administration was ineffective, leading to the initiation of extended NMV/r therapy. One week later, he exhibited elevated gamma-glutamyl transpeptidase (GGT) levels, and one month later, he developed AAC. Cholecystitis was successfully resolved via percutaneous transhepatic gallbladder drainage and administration of antibiotics. We speculate that extended NMV/r administration, in addition to COVID-19, may have contributed to the elevated GGT and AAC. During treatment of persistent SARS-CoV-2 infection with extended NMV/r therapy, patients should be carefully monitored for the appearance of findings suggestive of biliary stasis and the development of AAC.